Fast fashion consumption and its environmental impact: a literature review - OLIVAR APONTE, NADIA K.; Hernández, Andrés; Torres, Vianey; SMITH, ERIC D. (2024)
The fast fashion linear business model and its widespread consumption practices have instigated numerous environmental consequences, prompting extensive research into sustainable consumer behavior. This article conducts a thorough and quantitative analysis of the contemporary research landscape of the fashion industry and its ecological impact. Spanning from 2012 to 2023, our review explores 119 articles sourced from journals at the intersection of clean production and the fashion industry. The analysis reveals two central research focal points and identifies 77 keywords embedded in the knowledge base. Three overarching knowledge domains emerge from this exploration. We construct a cohesive narrative by synthesizing critical knowledge junctures, the knowledge base, and identified domains, resulting in a knowledge structure comprising five key concepts. Moreover, keywords are thoughtfully organized under their respective knowledge domains. As a synthesis of these insights, this article presents a robust knowledge roadmap, serving as a compass for a nuanced understanding of the current state of sustainability within the dynamic realm of the fashion industry.